Science Learning Problems and Solutions: A Case Study Analysis of Critical Thinking and Collaboration Abilities of MI/SD Students - Adisti Yuliastrin; Aziqri Aulia; Rian Vebrianto (Journal of Practice Learning and Educational Development, 2026)
The problem in education is that implementing learning is not as easy as practicing all learning theories and media. Therefore, the researcher aims to identify issues related to the implementation of learning concerning theories and learning media. The design of this research is a case study on the Methodology of Magnitudes and Units; this research uses a mixed method, where quantitative data on Learning Media is then reinforced with qualitative data. In this study, 4 science teachers and 22 fifth-grade MI students were involved. This research used interview, observation, and questionnaire instruments. Data were collected through direct field visits and analyzed using descriptive analysis for quantitative data and interview result analysis for qualitative data, making the obtained data comprehensive. The research results indicate that there is a low level of critical thinking skills and low collaboration skills, leading to the conclusion that it is necessary to design effective learning to enhance critical thinking and collaboration skills. Therefore, the recommendation/implication of this research is to implement an AR-assisted discovery learning model.